The dialectic of implicit systems in *Half of a Yellow Sun* by Chimamanda Ngozi Adichie - baadji, Ismahan (El Omda in Linguistics and Discourse Analysis, 2025)
The research paper aims to reveal the controversy of the cultural systems hidden behind the novel "Half of a Yellow Sun" by Chimamanda of Nigeria. This is based on the cultural criticism approach as a method that reveals implicit patterns within the fictional text. The novel revealed the existence of a class struggle fueled by customs, habits and tribal thought, which eventually led to the outbreak of a civil war that wiped out many of Nigeria's population.